(untitled) (Revista Brasileira de Iniciação Científica, 2024)
Light is one of the main factors controlling in vitro plant growth. This study aimed to evaluate the influence of LED light quality (white, red, blue, and red-blue) as well as the intensity of white LED light (15, 30, 60, and 75 μmol m-2 s-1) on the elongation of explants and production and growth of shoots in Apuleia leiocarpa. The use of white LED light resulted in greater vigor and size of shoots. Higher production of buds, shoots, and callus was observed at light intensities between 40 and 60 μmol m-2 s-1. The different light qualities and intensities tested allowed for in vitro growth of the species.